10 Epidemiology of population mortality related to falls in california 2000–2016: an increasing challenge for EMS. (26th April 2019) - Buzzacott, P; Ball, S; Brown, E; Tohira, H; Finn, J
Abstract : Background: Falls mortality increases with age and the U.S. population is aging steadily. This study examined the epidemiology of mortality in California this century due to unintentional falls. Method: Deaths caused by falls were extracted from California Department of Public Health data. Yearly Californian population estimates from the California Department of Finance were used to calculate the incidence of falls mortality. Results: There were 32 276 deaths attributed to falls, out of 618, 589, 117 person-years. Deaths at age ≥60 years accounted for 26 669 (83%). There were 15% more deaths during winter months, compared with summer. From age 70 mortality approximately doubled every five additional years of age. The age-adjusted falls mortality rate per 1 00 000 person-years (against the 2000 U.S. Standard Population) increased over 2000–2016 from 3.0 to 4.5 in females and from 8.9 to 9.8 in males. The number of falls deaths increased by a mean 77 per year, (95% CI 72, 83, R2=0.98, p<0.0001), doubling from 1251 in 2000 to 2582 in 2016. Conclusion: It may be prudent for EMS in California to anticipate continued increases in falls mortality. If the annual number of falls-related deaths continues to climb by an average of 77 deaths per year, then California will experience more than 3000 falls deaths per year sometime between 2025 and 2030. Recent increases were partly driven by a combination of increasing population and changes in the age distribution, however, age-adjusted mortality rates also increased, especially in females and older age groups. Conflict of interest: None. Funding: None.